Brief communication: Does climatic change in precipitation drive erosion in Naxos Island, Greece? - Nastos, P.; Evelpidou, N.; Vassilopoulos, A. (Natural Hazards and Earth Sciences (NHESS), 2010)
In this paper we examined whether the recorded precipitation changes cause erosion in Naxos Island, Greece using precipitation indices derived from daily precipitation totals, during the period 1955–2007, in order to develop an erosion risk model. Although the mean annual precipitation appear to be low (~360.0 mm), the erosion processes of the area are very intense, because of the intensive character of precipitation, the high slope relief, the differential lithology and the absence of important land cover The results of the analysis showed that the climatic changes in precipitation and the changes in land cover and land use are the main drivers for the erosion. This is why the 2nd (1971–1985) and 3rd (1986–2007) studied sub-periods may be called of high erosion risk, and especially the second one mainly because of the increased frequency of extreme precipitation events.